REDEFINISI ETNISITAS DALAM KONTEKS KEBUDAYAAN NASIONAL - Lan, Thung Ju (P2KK LIPI, 2006)
Ethnicity is a very important issue for the pluralistic Indonesian society, but before ethnic violences exploded in various places of Indonesia, not many social scientists were interested in studying the topic, and their understanding of ethnicity was mostly limited to the classic meaning of “an ethnic group’s identity” introduced by Fredrik Barth in 1969. This classic meaning has obviously failed to help us understand the dynamics of ethnic violences that occurred in Indonesia during the 7-8 years after the 1996 Sanggauledo conflict because it implied “old histories, local rivalries, and deep hatred” that could be traced back to the beginning of tribalism, but had no real connection to contemporary occurrences such as how ethnicity (of the Acehnese and the Papuan) was mobilized as ‘identity politics’ at the level of nation-state which led to state’s violences against those (ethnic) groups. Therefore, I think it is quite critical to discuss the new definition of ethnicity as ‘a new cultural dimension of difference’ and/or ‘the question of culturalism’, as well as its significance within the present socio-political context of Indonesia. For instance, is the (re)construction of ethnicity by the Acehnese, the Papuan, the Dayak, the Riau-Malay, and others in mobilizing ethnic solidarity really ‘the (re)making of ethno(local)-nationalism’ as some people have suggested? Keywords: etnicity, ethnic violence, difference, culturalism, ethno(local)- nationalism.